Particle Seeded Grains to Identify Highly Irregular Solid Boundaries and Simplify PIV Measurements - Basham, William; Budwig, Ralph; Tonina, Daniele (Frontiers in Earth Science, 2019)
Particle image velocimetry, PIV, is a non-invasive technique for measuring velocity fields. It is especially powerful when coupled with refractive index-matching (RIM) to map velocity fields around solid objects. The solid objects are typically removed from the flow field with a masking approach before performing the PIV analysis and mapping the velocity field, thus defined as an a-priori method. However, applying this method, with a mask of the correct shape and at the correct location, is difficult, time consuming and would be potentially unfeasible for packed bed of irregular shaped grains. To address this problem, we present the proof-of-concept of a novel approach to delineate highly irregular granular particles (grains) of varying size and shape and improve PIV processing for flows around grains in laboratory studies. The present technique makes use of seeding transparent RIM solids with light scattering particles during their fabrication. The RIM of the solids preserves the optical fidelity of images and the laser light sheet. Whereas the seeding in the solids can provide image contrast between solid (seeded) and fluid (non-seeded) as well as a strong zero-velocity signal in the solid. The fluid may then be seeded as well, allowing PIV spatial correlations to be performed with high confidence over the entire image. We tested the seeded RIM solid approach with both irregular individual solid pieces as well as with a volume of irregular grains. The new technique effectively obtains the fluid velocity field and solid boundary locations in both cases. Applications of the present method may range from studies of interstitial processes within a simulated sediment bed, such as those of aquifers, soils, sediments and the hyporheic zone, to near bed flow hydraulics.